Evaluation of Conflicts of Interest among Participants of the Japanese Nephrology Clinical Practice Guideline. Issue 6 (June 2022) - Murayama, Anju; Yamada, Kohki; Yoshida, Makoto; Kaneda, Yudai; Saito, Hiroaki; Sawano, Toyoaki; Shrestha, Sunil; Shrestha, Rajeev; Tanimoto, Tetsuya; Ozaki, Akihiko
Visual Abstract: Abstract : Background and objectives: Rigorous and transparent management strategies for conflicts of interest and clinical practice guidelines with the best available evidence are necessary for the development of nephrology guidelines. However, there was no study assessing financial and nonfinancial conflicts of interest, quality of evidence underlying the Japanese guidelines for CKD, and conflict of interest policies for guideline development. Design, setting, participants, & measurements: This cross-sectional study examined financial and nonfinancial conflicts of interest among all 142 authors of CKD guidelines issued by the Japanese Society of Nephrology using a personal payment database from all 92 major Japanese pharmaceutical companies between 2016 and 2019 and self-citations by guideline authors. Also, the quality of evidence and strength of recommendations underlying the guidelines and conflicts of interest policies of Japanese, US, and European nephrology societies were evaluated. Results: Among 142 authors, 125 authors (88%) received 6, 742, 889 in personal payments from 56 pharmaceutical companies between 2016 and 2019. Four-year combined median payment per author was 8258 (interquartile range, 2230‒51, 617). The amounts of payments and proportion of guideline authors with payments remained stable during and after guideline development. The chairperson, vice chairperson, and group leaders received higher personal payments than other guideline authors. Of 861 references in the guidelines, 69 (8%) references were self-cited by the guideline authors, and 76% of the recommendations were on the basis of low or very low quality of evidence. There were no fully rigorous and transparent conflicts of interest policies for nephrology guideline authors in the United States, Europe, and Japan. Conclusions: Most of the Japanese CKD guideline recommendations were on the basis of low quality of evidence by the guideline authors tied with pharmaceutical companies, suggesting the need for better financial conflicts of interest management.